Arriving at the Starting Line: The Impact of Community and Financial Logics on New Banking Ventures - Almandoz, Juan (Academy of Management Journal, 2012)
Building on the literature on competing logics and the context of local banks, I explore an important outcome for entrepreneurial efforts that is reaching the point of establishment. The embeddedness of founding teams in a community logic makes them more committed and more capable of attracting local support, resulting in greater establishment rates for their enterprises. By contrast, embeddedness in a financial logic leads to more likely team dissolution. High embeddedness in both logics simultaneously has a positive effect on the likelihood of establishment in stable economic periods, but a negative effect in turbulent periods. Qualitative evidence suggests that the existence of factions in a founding team—more likely in turbulent periods—could account for such a difference. Drawing on a mix of archival data on bank founding teams and interview data, this article links logics, founder backgrounds, and entrepreneurial success. Variation in founder backgrounds influences establishment rates for reasons that can be traced back to community and financial logics. This study thus links literatures on competing logics, founder motivations, and entrepreneurship. By showing the contingent effect of economic stability on the successful integration of logics within founding groups and thus on entrepreneurial establishment, this study also contributes to research on institutional complexity and ambidexterity.